Коваль А. П., Коптілов В. В. Крилаті вислови української літературної мови - Одрехівська, І. (Мовознавство, 2012)
Рецензія на книгу: Коваль А. П., Коптілов В. В. Крилаті вислови української літературної мови.— 3-є доп. вид. К .: Ярославів Вал, 2011. — 704 с.